2010
DOI: 10.1007/s10943-010-9399-7
|View full text |Cite
|
Sign up to set email alerts
|

Can Spirituality be Taught to Health Care Professionals?

Abstract: Although people with life-limiting conditions report a desire to have spiritual concerns addressed, there is evidence that these issues are often avoided by health care professionals in palliative care. This study reports on the longitudinal outcomes of four workshops purpose-designed to improve the spiritual knowledge and confidence of 120 palliative care staff in Australia. Findings revealed significant increases in Spirituality, Spiritual Care, Personalised Care, and Confidence in this field immediately fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 26 publications
1
36
0
2
Order By: Relevance
“…50 Finally, this curriculum provided explicit ethical guidelines for patient-centered spiritual care, often lacking in other workshops. [53][54][55][56] Our strategic goal for this training was to educate a variety of front-line clinicians to function as spiritual care generalists throughout the hospital. Board-certified chaplains are typically a scarce hospital resource.…”
Section: Discussionmentioning
confidence: 99%
“…50 Finally, this curriculum provided explicit ethical guidelines for patient-centered spiritual care, often lacking in other workshops. [53][54][55][56] Our strategic goal for this training was to educate a variety of front-line clinicians to function as spiritual care generalists throughout the hospital. Board-certified chaplains are typically a scarce hospital resource.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reflected the experience of physicians: one focused on residents in family medicine [49], and the other focused on palliative care physicians [50]. Four addressed interdisciplinary care teams: palliative care staff [51,52], medical directors and chaplains [53], multifaceted organizational perspective (nurses, patients, family, chaplains, and hospital administrators) [54]. One study focused both on nurses' educational outcomes from a training session, as well as patient outcomes [55].…”
Section: Key Pointsmentioning
confidence: 99%
“…A common theme throughout the literature was a call for training and education in spiritual care giving; two studies examined the experience of students learning spiritual care giving using qualitative inquiry methods [35,47]; nine were conducted pertaining to the efficacy of such training [30,31,39,41,43,48,49,52,55]. Educational sessions were found to be effective in clarifying what spirituality is, increasing care givers' confidence in providing spiritual care, and providing a context for care givers to examine their own spirituality.…”
Section: Educationmentioning
confidence: 99%
“…There is a need for healthcare professionals to increase their knowledge and confidence in addressing spiritual issues as part of healthcare services (Meredith et al 2012). Therefore, research has shown that spirituality has been a neglected aspect of education which appears to be a concern within spheres of interest in healthcare education and continues to evolve based on societal needs (Webster 2003;Borneman 2011;Morris 2013;Morris et al 2012;Puchalski 2001Puchalski , 2006King and Crisp 2005).…”
Section: Introductionmentioning
confidence: 99%